KINERJA PETUGAS APRON MOVEMENT CONTROL PADA BANDAR UDARA INTERNASIONAL SOEKARNO-HATTA - Tito Warsito; Dewa Kadek Anta Boga; Alit Sodikin (Institut Transportasi dan Logistik Trisakti, 2017)
The purpose of this study is to determine the factors causing the performance of AMC officers which is considered not optimal at Soekarno-Hatta International Airport from July to September 2013. This research method was using descriptive qualitative using fishbone theory, collecting data by giving questionnaires to 39 respondents, and using library data. The first factor is less skilled apron officers who are dealing with domestic and international flight problems (33%). The cause of the 2nd sequence is the apron officer is less engaged in the maintenance of the facilities and equipment used (27%). Management is not transparent in informing the reward system (20%). The cause of the problem in sequence 4 is that management is not giving much motivation to the apron officers (13%). The cause factor of sequence 5 is that the apron officers pay less attention to the cleanliness aspect of the apron area and the time of officers’ work (7%).